Kesepian sebagai faktor prediktif ide bunuh diri di kalangan mahasiswa: Studi pada mahasiswa Universitas Padjadjaran selama pandemi Covid-19: Loneliness as a predictor factor of suicidal ideation among college students: A study of Padjadjaran University students during the Covid-19 pandemic - Hamzah, Vania Diva Salsabila; Triwahyuni, Airin (Universitas Brawijaya, 2023)
The pandemic situation required the majority of universities to carry out online learning, including Universitas Padjadjaran. The pandemic situation tends to decrease students' probability to interact while doing academic activities. This study was conducted to prove whether loneliness can also predict the emergence of suicide ideation during pandemic Covid-19 using the R-UCLA Loneliness Scale and the Suicide Ideation Scale. The research sample was 171 active students from Universitas Padjadjaran, with 49 male participants and 122 female participants. 20.47% of participants had severe loneliness and 19.3% of participants had high level of suicide ideation. Simple regression test showed that loneliness can be used to predict 27.8% the occurrence of suicidal ideation in male participants and 30% in female participants. Further research can be done by balancing the number of male participants.